2020
DOI: 10.1097/wno.0000000000001148
|View full text |Cite
|
Sign up to set email alerts
|

Neuro-Ophthalmic Complications in Patients Treated With CTLA-4 and PD-1/PD-L1 Checkpoint Blockade

Abstract: Background: In recent years, CTLA-4 and PD-1/PD-L1 checkpoint inhibitors have proven to be effective and have become increasingly popular treatment options for metastatic melanoma and other cancers. These agents work by enhancing autologous antitumor immune responses. Immune-related ophthalmologic complications have been reported in association with checkpoint inhibitor use but remain incompletely characterized. This study seeks to investigate and further characterize the neuro-ophthalmic and ocular complicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…Neurological Autoimmunity Secondary to Immune Checkpoint Inhibitors ICI act by enhancing the immune response against cancers and are increasingly approved for treatment of different tumors. A common and unwanted effect of these drugs is autoimmunity, potentially directed against any organ (121)(122)(123)(124)(125). CNS autoimmunity may occur, generally within the first 3 months, and is accompanied by neural specific autoantibodies in approximately half of moderate-high severe cases.…”
Section: Cns Inflammation Secondary To Tnfα Inhibitorsmentioning
confidence: 99%
“…Neurological Autoimmunity Secondary to Immune Checkpoint Inhibitors ICI act by enhancing the immune response against cancers and are increasingly approved for treatment of different tumors. A common and unwanted effect of these drugs is autoimmunity, potentially directed against any organ (121)(122)(123)(124)(125). CNS autoimmunity may occur, generally within the first 3 months, and is accompanied by neural specific autoantibodies in approximately half of moderate-high severe cases.…”
Section: Cns Inflammation Secondary To Tnfα Inhibitorsmentioning
confidence: 99%
“…Although ocular irAEs are infrequent based on the previous study, they can cause a deterioration of the quality of life and exert an influence on the compliance of patients. Lots of studies have reported the ocular adverse events secondary to ICIs (19,25,26,30,31,153,(164)(165)(166)(167)(168) and the grade of the adverse events had been published recently based on Common Terminology Criteria for Adverse Events. While no study had reported the ocular irAEs in lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it can be unilateral or bilateral. According to previous studies, ophthalmoplegia in lung cancer secondary to ICIs were accompanied by myasthenia gravis (MG) in all patients ( 25 , 34 39 , 46 , 47 , 49 51 , 55 57 , 60 , 64 , 69 76 , 79 , 81 ). Ptosis is the key manifestation of immune-related MG, and accounts for 75%–78.7% of ICI-induced MG (irMG) ( 93 96 ).…”
Section: Clinical Characteristic Of Ocular Iraes In Lung Cancer With Icismentioning
confidence: 90%
See 2 more Smart Citations